Similar Skin Barrier Function in Persons with Type 1 Diabetes Compared with Healthy Controls - Berg, Anna Korsgaard; Grauslund, Annemarie Cecilie; Nørgaard, Kirsten; Thorsen, Steffen Ullitz; Zachariae, Claus; Halling, Anne-Sofie; Jakasa, Ivone; Kezic, Sanja; Svensson, Jannet; Thyssen, Jacob P. (JID innovations, 2023)
Contact dermatitis because of use of diabetes devices is frequent in individuals with type 1 diabetes (TD1), especially in the pediatric age group, but the putative role of a constitutional impaired skin barrier in persons with TD1 is unclear. This study examined the skin barrier function by the measurement of natural moisturizing factor and free cytokines collected through skin tape strips, as well as biophysical markers and the skin microbiome, in persons with TD1 than to age- and sex-matched healthy controls. All measurements were done in nonlesional skin. We found that the skin barrier function was similar in children and adolescents with TD1 than to controls but found that the beta-diversity of skin microbiome at the buttock differed between the two groups. We conclude that individuals with TD1 have normal skin barrier function, and that the increased occurrence of contact dermatitis following pump and sensor use is explained by exogenous factors. [Display omitted]